Vaso-occlusive retinopathy and stage IV Lupus Nephritis; Primary manifestation of a 30 year old female - Saiful, Tasnuva; Elahi, Quadrat E; Mostafi, Mamun; Mia, Abdul Ali (Bangladesh Journal of Medicine, 2018)
The diagnosis of systemic lupus erythematosus (SLE) depends on clinical evidence of renal, rheumatologic, cutaneous, and neurologic involvement, supported by serological markers. Ocular involvement is not included in diagnostic criteria of SLE. Vaso-occlusive retinopathy, as the primary manifestation of systemic lupus erythematosus (SLE), is relatively rare. We report a 30-year-old female, who suddenly suffered bilateral visual loss. Fundus examination revealed bilateral occlusive retinal vasculitis. She fulfilled the American College of Rheumatology criteria for diagnosing SLE; she had arthralgia, photosensitivity, positive ANA, high titre of anti-dsDNA, and proteinuria. A renal biopsy showed stage IV lupus nephritis. Treatment was initiated with pulse steroid and immunosuppressant. Best corrected visual acuity of both eye improved to finger counting after treatment. This case demonstrates that in patients with severe vaso-occlusive retinopathy, a generalized immunological disorder, like SLE, should be suspected. Bangladesh J Medicine Jan 2018; 29(1) : 36-40